Effect of interleukin 6 deficiency on renal interstitial fibrosis. - Jun Yang (Public Library of Science (PLoS), 2012)
Our recent studies have shown that bone marrow-derived fibroblast precursors contribute significantly to the pathogenesis of renal fibrosis. However, the molecular mechanisms underlying the recruitment and activation of bone marrow-derived fibroblast precursors are incompletely understood. We found that interleukin 6 was induced in the kidney in a murine model of renal fibrosis induced by unilateral ureteral obstruction. Therefore, we investigated if interleukin 6 play a role in the recruitment and maturation of bone marrow-derived fibroblast precursors in the kidney during the development of renal fibrosis. Wild-type and interleukin 6 knockout mice were subjected to unilateral obstructive injury for up to two weeks. Interleukin 6 knockout mice accumulated similar number of bone marrow-derived fibroblast precursors and myofibroblasts in the kidney in response to obstructive injury compared to wild-type mice. Furthermore, IL-6 knockout mice expressed comparable α-SMA in the obstructed kidney compared to wild-type mice. Moreover, targeted disruption of Interleukin 6 did not affect gene expression of profibrotic chemokine and cytokines in the obstructed kidney. Finally, there were no significant differences in renal interstitial fibrosis or expression of extracellular matrix proteins between wild-type and interleukin 6 knockout mice following obstructive injury. Our results indicate that interleukin 6 does not play a significant role in the recruitment of bone marrow-derived fibroblast precursors and the development of renal fibrosis.